Loyal to Commerce?: Merchants and the Occupation of Eastern North Carolina, 1862-1865 - Shuler, Noah S (East Carolina University, 2021)
This thesis comparatively analyzes the experiences and loyalties of merchants in the North Carolina towns of New Bern and Williamston during the American Civil War through the viewpoint of two individual merchants: Jacob Gooding Sr. and Cushing Biggs Hassell. The proximity of Federal occupation drastically affected the economic conditions that merchants experienced, but ultimately had little negative effect on merchant loyalties in the region. New Bern was occupied directly by Federal forced from 1862 to 1865, while Williamston remained on the frontier of Confederate territory but was plagued by repeated Federal raids. The distinctive identity, ideology, and culture of the Southern merchant class caused Confederate loyalty to prevail among merchants like Hassell and Gooding in both towns despite the promise of improved commercial self-interest offered by Federal authorities in New Bern or the destruction and damage caused by Federal raids in Williamston.
Keywords: Loyalty; Occupation; Commerce; Union; Confederacy; Merchants--North Carolina--History--19th century; North Carolina--History--Civil War, 1861-1865--Economic aspects; Williamston (N.C.)--History; New Bern (N.C.)--History